2018
DOI: 10.3389/fendo.2018.00413
|View full text |Cite
|
Sign up to set email alerts
|

“Luteal Analgesia”: Progesterone Dissociates Pain Intensity and Unpleasantness by Influencing Emotion Regulation Networks

Abstract: Background: Pregnancy-induced analgesia is known to occur in association with the very high levels of estradiol and progesterone circulating during pregnancy. In women with natural ovulatory menstrual cycles, more modest rises in these hormones occur on a monthly basis. We therefore hypothesized that the high estradiol high progesterone state indicative of ovulation would be associated with a reduction in the pain experience.Methods: We used fMRI and a noxious thermal stimulus to explore the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 78 publications
0
19
0
Order By: Relevance
“…It was suggested that differences in the responses between groups may be a result of less variability in hormones across the hormonal contraceptive cycle . Because RPE may be difficult to differentiate from pain, another explanation could be that RPE values at the end of the MLSS trial may have been affected by a decreased perception of pain in the mid‐luteal phase compared with the late‐follicular phase (known as the “luteal analgesia” effect) . Although it is unclear why perception of effort was different when all physiological responses remained the same, it would be interesting to know how this elevated RPE in the mid‐follicular phase would have affected performance during a longer ride.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that differences in the responses between groups may be a result of less variability in hormones across the hormonal contraceptive cycle . Because RPE may be difficult to differentiate from pain, another explanation could be that RPE values at the end of the MLSS trial may have been affected by a decreased perception of pain in the mid‐luteal phase compared with the late‐follicular phase (known as the “luteal analgesia” effect) . Although it is unclear why perception of effort was different when all physiological responses remained the same, it would be interesting to know how this elevated RPE in the mid‐follicular phase would have affected performance during a longer ride.…”
Section: Discussionmentioning
confidence: 99%
“…40 Because RPE may be difficult to differentiate from pain, another explanation could be that RPE values at the end of the MLSS trial may have been affected by a decreased perception of pain in the mid-luteal phase compared with the late-follicular phase (known as the "luteal analgesia" effect). 41 Although it is unclear why perception of effort was different when all physiological responses remained the same, it would be interesting to know how this elevated RPE in the mid-follicular phase would have affected performance during Table 3 and results section for statistical significances a longer ride. For example, if the MLSS ride was prolonged until volitional exhaustion, it is possible that these women not using oral contraceptives may disengage from the exercise trial earlier due to the greater perception of effort.…”
Section: Non-oral Contraceptive (N = 15)mentioning
confidence: 99%
“…Indeed, it has recently been postulated that "luteal analgesia" occurs in eumenorrheic females when progesterone is elevated, where the affective response to nociceptive pain is reduced due to alterations in functional connectivity in the emotional regulation network (69). Thus, it could be possible that the analgesic effects of enhanced GABAergic neurotransmission permitted participants to continue exercising for a longer period due to a lower perception of pain.…”
Section: Fatigability Across the Menstrual Cyclementioning
confidence: 99%
“…Studies of the impact of menstrual hormone changes on pain perception have found that high levels of progesterone, in the presence of high estradiol, produce a dissociation of the subjective pain rating and its unpleasantness such that, although pain is recognized, it is perceived as less distressing. 12 Investigation of this effect using functional magnetic resonance imaging techniques reveals a decreased connectivity between the inferior frontal gyrus (IFG), a region of the prefrontal cortex, and the amygdala. 12 The IFG has been found to modulate pain unpleasantness and links both to the nucleus accumbens, generating positive reappraisal of emotion, and to the amygdala, generating negative appraisals.…”
Section: Hormonesmentioning
confidence: 99%
“…12 Investigation of this effect using functional magnetic resonance imaging techniques reveals a decreased connectivity between the inferior frontal gyrus (IFG), a region of the prefrontal cortex, and the amygdala. 12 The IFG has been found to modulate pain unpleasantness and links both to the nucleus accumbens, generating positive reappraisal of emotion, and to the amygdala, generating negative appraisals. 13 This uncoupling of the IFG to the amygdala in the high-progesterone, high-estradiol state thus reduces the negative emotional bias applied to painful stimuli.…”
Section: Hormonesmentioning
confidence: 99%